The role of oxidized non-coding RNAs of the epigenome in the development of human diseases (literature review) - S.S. Ostrovska; Ye.N. Dychko; T.Ye. Shumna; G.I. Titov; O.S. Trushenko; P.G. Gerasymchuk; I.Y. Burega (Medičnì Perspektivi)
The attention of scientists to the role of the epigenome in the development of human diseases is associated with the discovery of new non-coding RNA molecules of the epigenome that affect gene expression with changes in protein function and the development of diseases. The study analyzed current scientific data on the effect of oxidative stress induced by cadmium on the regulatory mechanisms of the epigenome, resulting in the development of pathological changes in the body. The results of the study showed that cadmium manifests its toxicity by oxidizing micro RNAs and long RNAs that regulate gene expression without changing DNA/histone complexes. It has been shown that epigenetic disorders under the influence of cadmium-induced oxidative stress can be transmitted to offspring without changing the genotype, and these aberrant changes in non-coding RNA expression patterns are associated with aging, cancer, neurodegenerative, cardiovascular diseases, etc. Circulating micro RNAs that are sensitive to oxidative stress are reported to be potential biomarkers of cardiovascular diseases, including myocardial infarction, hypertrophy, ischemia/reperfusion, and heart failure. Many studies are aimed at using microRNAs for therapeutic purposes. The complete expression profile of microRNAs in human atherosclerotic plaques was studied, and the mechanisms affecting their formation were identified. Specific microRNAs and reactive oxygen species were identified as potential biomarkers in human malignancies, which expands the possibilities of their use as therapeutic targets. Unlike micro RNAs, the expression of long RNAs has tissue and species specificity, making them important candidates for specific disease markers. The role of these RNAs in carcinogenesis is being actively studied. A large number of them are disrupted at various types of cancer and may play an important role in the onset, metastasis, and therapeutic response of cancer. Thus, oxidative stress induced by cadmium affects non-coding RNAs, which disrupts the regulatory mechanisms of the epigenome and affects the development of cardiovascular, oncological, pulmonary and other human diseases. The search for the impact of non-coding RNAs on the epigenome is constantly growing and has great scientific and practical prospects in medicine.